PENERAPAN SISTEM INFORMASI KEPEGAWAIAN DINAS PENDIDIKAN (SIMPEGDIK) DI SMAN 4 TAKALAR - Nasmin, Andi Nur Asnani; Damopolii, Muljono; Hasan, Madhiah (Department of Islamic Education Management, 2024)
The purpose of this study is to determine the application of sympegdik at SMAN 4 Takalar. The research applies qualitative research, where researchers can adopt methods of starting to understand the phenomena that are the focus of research, directly involved in the research field through participatory observation, and provide space for impressions and understanding that emerge. The main source of data in this study involved school operators and teachers at SMAN 4 Takalar. In addition, secondary data obtained from books, journals, and related research that have been conducted by other researchers, become a source of supporting information. The results of this study show that SMAN 4 Takalar has implemented Simpegdik, among others: 1) Implementation of the Education Office Personnel Information System (Simpegdik); 2) Functions and Benefits of Simpegdik at SMAN 4 Takalar; 3) Challenges of implementing simpegdik at SMAN 4 Takalar. To ensure the validity of the data in this study, observation, interview, and document analysis techniques were used. The data triangulation process is also applied to three stages of data management and analysis, namely data reduction, data presentation, and conclusions, to check the accuracy of information. Conclusion based on The implementation of simpegdik at SMAN 4 Takalar is considered successful, providing benefits for all parties involved.